12-oxo-Phytodienoic Acid: A Fuse and/or Switch of Plant Growth and Defense Responses? - Liu, Wenshan; Park, Sang-Wook (Frontiers in Plant Science, 2021)
12-oxo-phytodienoic acid (OPDA) is a primary precursor of (-)-jasmonic acid (JA), able to trigger autonomous signaling pathways that regulate a unique subset of jasmonate-responsive genes, activating and fine-tuning defense responses, as well as growth processes in plants. Recently, a number of studies has illuminated the physiol-molecular activities of OPDA signaling in plants, which interconnect the regulatory loop of photosynthesis, cellular redox homeostasis and transcriptional regulatory networks; together shedding new light on i) the underlaying modes of cellular interfaces between growth and defense responses (e.g., fitness tradeoffs or balances), and ii) vital information in genetic engineering or molecular breeding approaches to upgrade plants’ own survival capacities. However, our current knowledge regarding its mode of actions is still far from complete. This review will briefly revisit recent progresses on the roles and mechanisms of OPDA and information gaps within, which help understanding the phenotypic and environmental plasticity of plants.